An Attempt to Establish the Scale and Orientation of the "œMap of Lobzow with Its Environs" - Banasik, Piotr (Geomatics and Environmental Engineering, 2021)
This work concerns the assessment of the cartometricity of the 19th century plan of the village of Lobzow near Krakow in Poland, known as "œMapa Łobzowa z przyległościami". The plan has not been researched in this respect so far. The aim of this study was to establish its scale and orientation in relation to directions of the world. A high resolution raster of the plan provided by the Historical Museum of the City of Krakow was used for the study. At first, an attempt was made to clarify the date of the plan´s origin. An analysis of information contained in archival documents shows that the plan of Lobzow was most probably created between 1824 and 1852, which corresponds with the period when the largescale cadastral map was developed in Galicia. Therefore, selected sections of this map, from the area covered by the plan, were used for research. The scale value of the Lobzow plan was calculated using the lengths of sections between selected points on the plan and map. The calculated plan scale is close to the scale of the detailed map section detailed sheet of the cadastral map. It was established that the plan of Lobzow has the orientation relative to magnetic north as was common in the first half of the 19th century. The mutual dependencies between the orientation of the plan and the cadastral map in relation to the direction of true geographical north were illustrated. The final result of the work was to show the changes in the topography of Lobzow that have taken place over nearly 200 years.